Domain Reuse Guidelines - Ramachandran, Muthu (INFOCOMP Journal of Computer Science, 2005)
In this paper, we discuss the general area of software development for reuse and reuse guidelines. We identify, in detail, language-oriented and domain-oriented guidelines whose effective use affects component reusability. This paper also proposes a tool support which can provide advise and can generate reusable components automatically and it is based on domain knowledge (reuse guidelines represented as domain knowledge).